Revacept, a Novel Inhibitor of Platelet Adhesion, in Patients Undergoing Elective PCI—Design and Rationale of the Randomized ISAR-PLASTER Trial - Schüpke, Stefanie; Hein-Rothweiler, Ralph; Mayer, Katharina; Janisch, Marion; Sibbing, Dirk; Ndrepepa, Gjin; Hilz, Raphaela; Laugwitz, Karl-Ludwig; Bernlochner, Isabell; Gschwendtner, Sarah; Kupka, Danny; Gori, Tommaso; Zeiher, Andreas M.; Schunkert, Heribert; Massberg, Steffen; Kastrati, Adnan; for the ISAR-PLASTER-Trial Investigators (Thrombosis and Haemostasis, 2019)
Despite dual antiplatelet therapy patients undergoing percutaneous coronary intervention (PCI) continue to experience periprocedural ischemic events. In addition, all currently used antithrombotic drugs increase the bleeding risk. Thus, there is an unmet clinical need for antithrombotic strategies with improved efficacy and no increase in bleeding. Revacept is a novel, lesion-directed antithrombotic drug that does not interfere with the function of circulating platelets. This dimeric fusion protein of the extracellular domain of glycoprotein VI (the major platelet collagen receptor) and the human Fc-fragment inhibits collagen-mediated platelet adhesion and subsequent aggregation at the site of vascular injury. The randomized, double-blinded, phase II ISAR-PLASTER trial is based on extensive preclinical evaluation of Revacept and a favorable first-in-man trial. A total of 332 patients with stable coronary artery disease undergoing elective PCI will be randomized to either Revacept 160 mg, Revacept 80 mg, or placebo administered as single intravenous infusion directly before the intervention, on top of standard dual antiplatelet therapy and either heparin or bivalirudin, based on local practice and current guidelines. The primary endpoint is the composite of death or myocardial injury (defined as increase in high sensitivity troponin T ≥ 5 times the upper limit of normal) at 48 hours. The safety endpoint is bleeding of class 2 or higher according to the Bleeding Academic Research Consortium at 30 days. This phase II randomized, double blind trial will assess for the first time the efficacy and safety of Revacept—a lesion-directed inhibitor of platelet adhesion—in patients undergoing elective PCI.
Keywords: Revacept; glycoprotein VI; platelet inhibitor; PCI; stabile angina